Towards Clean River Through Distributed Community Based Waste to Energy - Aria Aditya; Supriadi Legino; Doddy Hertanto; Hany Stenvil (Nusantara Science and Technology Proceedings, 2021)
Municipal waste is the main source of challenges to ensure a clean river, with the main cause being a lot of its citizens still throw their plastic bags full of waste into the river, as if the river is a public moving garbage container. The purpose of this study is to conduct a benefit-cost analysis of applying the new way of community-based waste treatment (CBWT) that has been successfully applied as a pilot project at various places including the office area of Gerakan Ciliwung Bersih (GCB). The research is a case study analysis method based on real data taken from the ongoing CBWT units that can convert a ton of waste into approximately 300 kg of pellet with around 3,000 kCal/kg bio-coal using microbiological treatment. The case studies in more than 15 places revealed that the capital expenditure of CBWT is around IDR 497,200, 000 and its operational expenditure is IDR 280,970,000 may potentially be profitable to attract small businesses that run these CBWT services. The proposition of this study is the more CBWT business units, the cleaner the river will be and in addition, it will also give social and environmental benefit as it will create employment opportunities and reducing Green House Gasses In this study, the financial, social, and environmental aspects will be calculated by using simulation.